The miracle worker - Bergen-Bishop, Suzy; Merrick, Monte; Tass, Nadia; Elliot, Alison; Eisenberg, Hallie Kate; Black, Lucas, 1982-; Goldstein, William 1942-; Gibson, William, 1914-; Walt Disney Home Video (Burbank, Calif. : Disney Home Video, 2000)
Depicts the story of Helen Keller and her guardian, Annie Sullivan, who broke through Helen's barriers of blindness and deafness to communicate with her
Based on the play by William Gibson
Title from title screen
Director of photography, David Parker ; production designer, Lindsey hermer-Bell ; editor, Maryann Brandon ; music, william Goldstein
Cast : Alison Elliot, Hallie Kate Eisenberg, Lucas Black
Keywords: Keller, Helen, -- 1880-1986 -- Drama; Sullivan, Annie -- 1866-1936 -- Drama; Gibson, William, -- 1914- -- Film and video adaptations; Television movies; Television adaptations